LEGAL EFFORT AGAINST CHILDREN AS VICTIMS OF DOMESTIC VIOLENCE (KDRT) - Ismaidar, Ismaidar; Rahmayanti, Rahmayanti (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
Children are a mandate and gift from God Almighty, who has inherent dignity and worth as a whole human being. Children are also the next generation of the nation's ideals and human resources for future national development.Domestic violence often occurs in human life.The protection of a child against the law and the elimination of crime and violence in a household are very interesting problems to study and research because children are the potential and successors of the nation's cadres which have basically been placed by the previous generation. The formulation of the problem is how to take legal action against children as victims of Domestic Violence (KDRT). Efforts to protect children must be carried out as early as possible, so that in the future children can participate optimally and can socialize in the surrounding environment and also as heirs and continuation of the future of a nation and state. Efforts to protect children need to be implemented firmly. Article 1 paragraph (2) of Law Number 23 of 2002 concerning Child Protection.The purpose of this research is to find outlegal protection for children as victims (Domestic Violence (KDRT) and legal remedies against children as victims of Domestic Violence (KDRT).This research uses descriptive analytical research method, the approach used is normative juridical. The approach method used in this research is the statutory approach.